Using caregiver report on the impact of challenging behavior exhibited by children with autism spectrum disorder to guide treatment development and outcomes. (8th August 2019) - Scheithauer, Mindy; Muething, Colin S.; Silva, Meghan R.; Gerencser, Kristina R.; Krantz, Joelle; Call, Nathan A.
Abstract : Objectives: Evaluations of treatments using applied behavior analysis (ABA) for challenging behavior have relied mostly on direct behavioral observation. While observation is crucial, qualitative information can also be beneficial. In this study, we describe methods for using qualitative information in ABA treatments for challenging behavior. Method: Three participants were undergoing treatment for challenging behavior. Information was collected through caregiver interviews at the start and end of the admission. Directed content analysis identified themes in the interviews and we compared treatment outcomes using qualitative and quantitative measures. Results: Three themes emerged: description, frequency, and impact of the behavior. Quantitative and qualitative measures both suggested successful interventions for two participants. For the third, direct observation suggested treatment was effective while caregiver report did not. Conclusion: Incorporation of qualitative information into outcomes allowed for a more comprehensive view of treatment success and guided assessment and treatment decisions. Treatments based on applied behavior analysis (ABA) are commonly studied for the treatment of challenging behavior, but these studies rely mostly on direct behavioral observation. While observation is crucial, qualitative information is also useful in ensuring meaningful results. In this study, we describe a method of collecting, analyzing, and using qualitative information collected from caregivers and compare qualitative to quantitative outcomes.